A Comprehensive Database Management System for a Variety of Clinical Trials - Koval, J. J.; Kwarciak, L. M.; Grace, M. G. A.; Lockwood, B.J. (Methods of Information in Medicine, 1987)
A multicentre database management system has been developed which permits individual centres to enter, update, and retrieve their data while allowing detailed analysis to take place on a multicentre basis. Individual centres can access only their own data; summaries, reports and graphics output can be used as a teaching device for seminars and rounds. In one instance, the system provides interactive services to 12 kidney transplant centres spanning a distance of 5000 kilometres; the database contains 20,000,000 items.The database management system is discussed and comparisons are made with other available systems.
Keywords: Database Management; Multicentre Clinicial Trial